State Ethics as the Basicof Legal Policy for Handling of Covid-19 in Indonesia - Hoesein, Zainal Arifin; Halim, Pathorang; Arifuddin, Arifuddin (International Journal of Criminology and Sociology, 2021)
The Covid-19 pandemic has created emergencies in all sectors of life around the world. In this context, this study seeks to evaluate the important role of state officials and administrators’ ethics as the basis for legal policy in handling Covid-19 in Indonesia. By using a descriptive method with a conceptual approach based on normative-juridical analysis, the results of the study show that law-making and policy implementation in handling Covid-19 should be based on an agreement of ethical, moral, and basic norms as basic legal values. In this context, the constitution must be used as the basis for ethics and moral values in which all State policies as outlined in the form of laws are guided by and by the 1945 Constitution. The conclusions of this study underline the implementation of ethics following the state constitution and theoretically contribute to the constitutional aspect in public policy where policy decisions on handling Covid-19 must remain following the constitution.